Immunotherapy and Prognosis of Non-small Cell Lung Carcinoma by Monomethoxy polyethylene glycol-hyaluronic acid-platinum Combined with Immune CT4+ and CT8+ Detection: Immunotherapy and Prognosis of Non-small Cell Lung Carcinoma - Ren, Xubin; Luo, Tong; Ma, Hailong; Zhou, Meili; Yu, Shufang (Cellular and Molecular Biology, 2022)
To investigate the changes in CT4+ and CT8+ lymphocyte subpopulations of patients with non-small cell lung carcinoma (NSCLC) by monomethoxy polyethylene glycol-hyaluronic acid-platinum (MPEG-HA-Pt) and the correlation between efficacy evaluation and the changes in T lymphocyte subpopulation, 76 NSCLC patients treated at oncology department of Chengdu First People’s Hospital were selected and randomly divided into the treatment group and the control group (38 cases in each). mPEG-HA-Pt was used for the treatment of the included patients in the research. The patients in the control group were performed with traditional chemotherapy for 2 treatment courses. The changes in the T-lymphocyte subpopulation before and after the treatment were detected and the therapeutic effects on the patients in the two groups were compared. The particle size of mPEG-HA-Pt ranged between 78nm and 100nm with an average of 84.6±7.5nm. After that, a transmission electron microscope (TEM) was used to observe the spheres with uniform size. The drug loading capacity and entrapped efficiency of mPEG-HA-Pt were 18.7% and 87.4%, respectively. After the treatment for NSCLC patients by nanomicelle, cellular immune functions were all improved. In particular, cellular immune functions of the patients with good efficacy evaluation were improved more apparently.